1996
DOI: 10.1113/expphysiol.1996.sp003955
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondria‐rich cells in epithelial chloride uptake

Abstract: SUMMARYUptake of NaCI by amphibian tight epithelia, such as skin, urinary bladder and collecting duct, requires considerable thermodynamic work. By calculation it is demonstrated that NaCi absorption from dilute external solutions ([NaCl] 1 mM) demands more energy than can be provided by the Na+-K+-ATPase alone. Thus, in addition to the Na+ pump, another transport ATPase must be involved. Previously, we have suggested that the other transport ATPase is an apical proton pump in mitochondria-rich (MR) cells. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Ϫ exchanger in frog skin (11,23). A similar mechanism has been proposed in gills of freshwater fishes (7,27,29); however, the exact sites for H ϩ secretion are still a controversial subject (see introduction).…”
Section: Discussionmentioning
confidence: 80%
“…Ϫ exchanger in frog skin (11,23). A similar mechanism has been proposed in gills of freshwater fishes (7,27,29); however, the exact sites for H ϩ secretion are still a controversial subject (see introduction).…”
Section: Discussionmentioning
confidence: 80%
“…These studies have identified cells that have been proposed to be analogous to ICs in the kidney, based on the fact that they independently exchange Na + for H + and Cl -for HCO 3 - (Larsen et al, 1996;Ehrenfeld and Klein, 1997;Jensen et al, 2003), using a proton-motive force attributed to a H + v-ATPase pump related to that in mammalian ICs Jensen et al, 2002). Here, we provide evidence that cells remarkably similar to the ICs of the mammalian kidney arise in the Xenopus larval skin.…”
Section: Discussionmentioning
confidence: 99%
“…Since fluid secreted into the tubule lumen is not sufficiently acidic to drive cation/H + antiport, the pH of an unstirred layer in the brush border might be low enough, as in amphibian skin (Larsen et al, 1996). In addition, large negative surface charges of the apical membrane due to fixed negative charges of glycosylated proteins, glycolipids and adsorbed proteins may support a surface pH considerably lower than that in the aqueous solution of the tubule lumen (Aronson and Giebisch, 1997).…”
Section: Atpase Activitiesmentioning
confidence: 99%